CREATIVITY IS NOT ENOUGH: UNLOCKING ENTREPRENEURIAL READINESS THROUGH SELF-EFFICACY AND AUTHORITATIVE PARENTING - Miswanto Miswanto; Tiara Nur Anisah; Kartinah Kartinah (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2026)
This study addresses the critical